THE PROCESS OF THE ACTIVITY OF THE FOREIGN POLICY OF THE RUSSIAN EMPIRE TO CENTRAL ASIA IN THE MIDDLE OF THE XIX CENTURY - Dilshod Baratov (Social science and innovation, 2023)
This article analyzes the activation of the Russian Empire’s foreign policy towards Central Asia in the middle of the 19th century and the factors that caused it. The activities in the Turkestan area started during the period when the Russians were competing with the British in this area. This article analyzes active foreign political relations and strategic goals of the Russian Empire with Central Asian countries.